squares and the sevens

Algebra Level 3

The infinite sum 1+4÷7+9÷7^2+16÷7^3+.....equals:

49÷27 27÷14 21÷13 256÷147

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mas Mus
Apr 27, 2015

Let x = 1 + 4 7 + 9 7 2 + 16 7 3 + ( 1 ) multiply (1) by 1 7 1 7 x = 1 7 + 4 7 2 + 9 7 3 + ( 2 ) ~~x=1+\dfrac{4}{7}+\dfrac{9}{7^2}+\dfrac{16}{7^3}+\ldots\quad (1)\rightarrow \text{multiply (1) by}~\frac{1}{7} \\ \dfrac{1}{7}x=~~~~~\dfrac{1}{7}+\dfrac{4}{7^2}+\dfrac{9}{7^3}+\ldots\quad ~(2)

Subtracting ( 1 ) to ( 2 ) (1)~ \text{to}~(2) , we have

6 7 x = 1 + 3 7 + 5 7 2 + 7 7 3 + ( 3 ) again, multiply (3) by 1 7 6 49 x = 1 7 + 3 7 2 + 5 7 3 + ( 4 ) \dfrac{6}{7}x=1+\dfrac{3}{7}+\dfrac{5}{7^2}+\dfrac{7}{7^3}+\ldots\quad ~(3)\rightarrow \text{again, multiply (3) by}~\frac{1}{7}\\ \dfrac{6}{49}x=~~~~~\dfrac{1}{7}+\dfrac{3}{7^2}+\dfrac{5}{7^3}+\ldots\quad ~(4)

again, subtracting ( 3 ) to ( 4 ) (3)~ \text{to}~(4) , so

36 49 x = 1 + ( 2 7 + 2 7 2 + 2 7 3 + ) \dfrac{36}{49}x=1+\left(\dfrac{2}{7}+\dfrac{2}{7^2}+\dfrac{2}{7^3}+\ldots\right)

In the last equation, on RHS in bracket, we have an infinite geometric progression with first term 2 7 \frac{2}{7} and common ratio 1 7 \frac{1}{7} . Thus

36 49 x = 1 + 2 7 1 1 7 = 4 3 x = 4 × 49 3 × 36 = 49 27 \dfrac{36}{49}x=1+\dfrac{\frac{2}{7}}{1-\frac{1}{7}}=\dfrac{4}{3}\\x=\dfrac{4\times{49}}{3\times{36}}=\boxed{\dfrac{49}{27}}

But, otherhand, we can use Arithmetic-Geometric Progression on the equation ( 3 ) (3) . Based on Arithmetic-Geometric Progression on RHS in equation ( 3 ) (3) , we have a = 1 , r = 1 7 , and d = 2 a=1, r=\dfrac{1}{7}, \text{and}~d=2 . Then,

6 7 x = 1 1 1 7 + 2 × 1 7 ( 1 1 7 ) 2 = 7 6 + 14 36 = 56 36 x = 56 × 7 36 × 6 = 49 27 \dfrac{6}{7}x=\dfrac{1}{1-\frac{1}{7}}+\dfrac{{2}\times{\frac{1}{7}}}{\left(1-\frac{1}{7}\right)^2}=\dfrac{7}{6}+\dfrac{14}{36}=\dfrac{56}{36}\\x=\dfrac{56\times{7}}{36\times{6}}=\boxed{\dfrac{49}{27}}

Good solution

Sai Ram - 5 years, 11 months ago

Solution by Mas Mus is no doubt very cool. But to think of such a solution is not so easy. I use TI-83 Plus calculator and set as follows. 1 S T R A E N T E R . 1 S T R X E N T E R . X + 1 S T R X : A + 7 X 2 7 n S T R A 1 ~STR~A~ENTER.~1~ STR~X~ENTER.\\X+1~ STR~ X~ : A+\dfrac{7*X^2}{7^n}~ STR~ A
press ENTER m times and we get sum of (m+1) terms. Aftter m=15, I got the sum as 1.814814815 for next several pressings of ENTER.. Now this suggested .814814815 is actually recurring 0.814. And that is 22 27 . S o t h e a n s w e r i s 1 22 27 = 49 27 . \dfrac {22}{27}. ~So~ the~ answer~ is~ 1\dfrac{22}{27}=\dfrac {49}{27}.
Logically, we see that after m=15, the term added is in the order of E 10 E^{-10} . So at m=15 we almost get the sum. Beyond it is out of calculator accuracy.

Charles Dutertre
May 14, 2015

Here is a solution that use power series, of course it's quite a big tool for this but this is an alternative to the (better) solution already given :)

Let us name S S the result, and define on ] 1 , 1 [ ]-1,1[ f the following power series f ( x ) = n = 0 n 2 x n f(x) = \sum_{n=0}^\infty n^2x^n such that we have S = f ( 1 / 7 ) S=f(1/7) .
Let us now define on ] 1 , 1 [ ]-1,1[ g such as g ( x ) = n = 0 x n g(x) = \sum_{n=0}^\infty x^n One can easily check that g ( x ) = 1 1 x g(x) = \frac{1}{1-x} (by seeing that 1 + x + x 2 + . . . + x N ) ( 1 x ) = 1 x N 1+x+x^2+...+x^N)(1-x) = 1-x^N , and making N N go to infinity) Also, f ( x ) = 1 ( 1 x ) 2 = 0 n x n 1 = 1 n x n 1 f'(x) = \frac{1}{(1-x)^2} = \sum_0^\infty nx^{n-1} = \sum_1^\infty nx^{n-1} = 1 ( n 1 ) x n 1 + 1 x n 1 = 0 n x n + f ( x ) = \sum_1^\infty(n-1)x^{n-1}+\sum_1^\infty x^{n-1} = \sum_0^\infty nx^{n}+f(x) Then f ( x ) = 2 ( 1 x ) 3 = g ( x ) + f ( x ) f''(x) = \frac{2}{(1-x)^3} = g(x) + f'(x) , and we just need to evaluate g g in 1 / 7 1/7 , as we now have the following expression :

g ( x ) = 2 ( 1 x ) 3 1 ( 1 x ) 2 = ( 2 1 x 1 ) 1 ( 1 x ) 2 g(x) = \frac{2}{(1-x)^3} - \frac{1}{(1-x)^2} = \left(\frac{2}{1-x}-1\right)\frac{1}{(1-x)^2}

g ( 1 / 7 ) = ( 2 7 / 6 1 ) ( 7 / 6 ) 2 = 8 49 6 36 = 2 3 7 2 2 3 3 3 = 49 27 g(1/7) = (2 \cdot 7/6 - 1 ) (7/6)^2= \frac{8 \cdot 49}{6 \cdot 36} = \frac{2^3\cdot 7^2}{2^3\cdot3^3} = \frac{49}{27}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...